The Potential Effect of the IDH1 Mutation and MGMT Gene Promoter Methylation on the Control of Glioblastoma-Associated Epilepsy in Patients Receiving Anti-Epileptic Agents and Chemotherapies - Maher KURDI; Nadeem Shafique BUTT; Saleh BAEESA; Badrah ALGHAMDI; Yazid MAGHRABI; Anas BARDEESI; Rothaina SAEEDI; Fahad ALGHAMDI; Najla ALGHANMI; Mohammed BARI; Alaa SAMKARI; Ahmed LARY; et al. (Archives of Epilepsy, 2021)

(untitled)
Objectives:(a) The objective of the study was to assess the control of seizure in glioblastoma patients receiving anti-epileptic drugs and chemotherapies after total resection and its association with O-methylguanine-DNA methyltransferase (MGMT) promoter methylation and the isocitrate dehydrogenase 1 (IDH1) mutation; (b) to determine which anti-epileptic drug exerts the best effective control on glioblastoma-associated epilepsy; and (c) to identify the relationship between seizure control and anti-epileptic drugs with recurrence interval.Methods:This was a retrospective cohort study of patients with postoperative glioblastoma-associated epilepsy. The correlation between IDH1 mutation and MGMT methylation with anti-epileptic drugs, chemotherapy type, seizure control, and recurrence interval was analyzed.Results:The study included 53 patients with glioblastoma-associated epilepsy. IDH1 mutation was present in 20 patients, and MGMT methylation was present in 13 patients. 37 cases received chemoradiotherapy while 16 cases received only radiotherapy. Levetiracetam was the most prescribed anti-epileptic drug (n=36, 60%), and 36 and 16 patients had controlled and uncontrolled seizures, respectively. IDH1 mutation and unmethylated MGMT were significantly present in cases with controlled epilepsy (p<0.05). Levetiracetam showed significantly better seizure control in cases with IDH1 mutation and unmethylated MGMT promotor (p<0.05).Conclusion:(a) Glioblastoma-associated epilepsy can be better controlled in patients with the IDH1 mutation and unmethylated MGMT, (b) levetiracetam was the first-line anti-epileptic drug for controlling seizure, (c) lack of seizure control in glioblastoma patients may not be related to tumor recurrence despite 1-year treatment, and (d) better understanding of the risk factors associated with glioma-associated epilepsy are needed to improve patient quality of life.